Automation facilities for agricultural machinery control - A. Yu. Izmaylov (Сельскохозяйственные машины и технологии, 2017)
The possibility of use of the automation equipment for agricultural machinery control is investigated. The authors proposed solutions on creation of the centralized unified automated information system for mobile aggregates management. In accordance with the modern requirements this system should be open, integrated into the general schema of agricultural enterprise control. Standard hardware, software and communicative features should be realized in tasks of monitoring and control. Therefore the schema should be get with use the unified modules and Russian standards. The complex multivariate unified automated control system for different objects of agricultural purpose based on block and modular creation should correspond to the following principles: high reliability, simplicity of service, low expenses in case of operation, the short payback period connected to increase in productivity, the reduced losses when harvesting, postharvest processing and storage, the improved energetic indices. Technological processes control in agricultural production is exercised generally with feedback. The example without feedback is program control by temperature in storage in case of the cooling mode. Feedback at technological processes control in agricultural production allows to optimally solve a problem of rational distribution of functions in man-distributed systems and forming the intelligent ergonomic interfaces, consistent with professional perceptions of decision-makers. The negative feedback created by the control unit allows to support automatically a quality index of technological process at the set level. The quantitative analysis of a production situation base itself upon deeply formalized basis of computer facilities that promotes making of the optimal solution. Information automated control system introduction increases labor productivity by 40 percent, reduces energetic costs by 25 percent. Improvement of quality of the executed technological operations will increase crop productivity by 1.2-1.3 times.